The Perceptual Evaluation of Clothing Sustainable Color in Clothing Design (Journal of Fiber Bioengineering and Informatics, 2024)
To investigate the aesthetic preferences of consumers towards various sustainable colors, this study aimsto assist designers in gaining a comprehensive understanding of consumers’ color preferences duringthe development of eco-friendly clothing designs. The study begins by establishing a sustainable colormatching scheme for clothing and employs the semantic difference method to select perceptual word pairs.Subsequently, a questionnaire survey is conducted to understand consumers’ perceptual evaluation ofsustainable colors in clothing. The study further analyzes and ranks the main factors by quantifyingthe perceptual evaluation and employing the grey correlation degree method. The results indicatethat temperament factor, personality factor, and coordination factor are the primary perceptual factorsinfluencing sustainable color. Among these factors, temperament exhibits the strongest correlation withthe degree of liking, followed by personality and coordination. When selecting colors, designers shouldprioritize low brightness and low purity colors. Additionally, blue-green colors are more favored byconsumers. The research findings hold significant implications for guiding designers in enhancing thequality and standard of green clothing design while meeting consumers’ perceptual cognitive requirements.